Honouring Jan Karol Chodkiewicz, the Voivode of Vilnius: Ποιημάτιον Honorarium to the New Voivode of Vilnius, to the Brightest Gentleman Jan Karol Chodkiewicz by Jonas Horskis (1617) - Narbutas, Sigitas (Senoji Lietuvos literatūra, 2024)
The publication discusses the depiction of Jan Karol Chodkiewicz (1571–1621), the great hetman of Lithuania and the voivode of Vilnius in early Neo-Latin Lithuanian literature, with stronger focus on the occasional Ποιημάτιον Honorarium to the New Voivode of Vilnius, to the Brightest Gentleman Jan Karol Chodkiewicz by Jonas Horskis (1617). With this work, the author immortalises several significant events in the history of Lithuania: the death of Benediktas Vaina, the bishop of Vilnius, the death of Mikolaj Krzysztof Radziwill, the voivode of Vilnius, the ingress of Eustachijus Valavičius, the new bishop of Vilnius, and the inauguration of Jan Karol Chodkiewicz, the new voivode of Vilnius. During the inauguration, the mayor of Vilnius, Tomas Digonis, presented a golden cup to the latter, on which the most important life events of his father Jan Hieronimowicz Chodkiewicz and Jan Karol Chodkiewicz himself before 1617 were depicted. The descriptions of the ingresses of the bishop and the voivode and the ingenious singing of the marches to Jan Hieronomowicz and Jan Karol impart novelty and originality to this work. The publication includes a translation of this work into Lithuanian.
Keywords: Jan Karol Chodkiewicz; Tomas Digonis; Jonas Horskis; Mikolaj Krzysztof Radziwill; Benediktas Vaina; Eustachijus Valavičius; voivode of Vilnius; Polish-Swedish War (1600–1611); Battle of Kircholm; Neo-Latin poetry; early Lithuanian literature